Pelaksanaan Penilaian Keterampilan dengan Teknik Portofolio pada Peserta Didik Sekolah Dasar di Kabupaten Sijunjung - Muhammad Feri; Andi Prastowo (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
Skills assessment aims to determine the ability of students in the practice of the material taught by the teacher. However, the assessment of skills is sometimes carried out by teachers only with feelings towards students. The purpose of this study was to determine the implementation of portfolio assessment of elementary schools. The method used in this research is a qualitative approach to the case study model. The population used for this research is the third grade students of the 25 Langki State Elementary School (SD N) Sijunjung Regency, amounting to 36 people. Data analysis was done by observing and interviewing the class teacher. The conclusion of this study describes the form of implementation of portfolio assessment in elementary schools which shows that the implementation of portfolio assessment for third grade students at SD N 25 Langki has been carried out by teachers in accordance with portfolio assessment indicators. Based on the indicators of observations and interviews that have been carried out by the teacher.